Improving Journal Article Tag Suite for multilingual articles - Vincent Lizzi (Science Editing, 2022)
The scenarios for journal articles that contain more than one language are no longer (and never really were) limited to having an article’s title, abstract, and keywords translated to additional languages. Journal Article Tag Suite (JATS) currently has a variety of structures for tagging articles that are in multiple languages or have substantial amounts of content in more than one language. However, these structures are not all coherent and are not up to the tasks of handling some common use cases. A subcommittee of the National Information Standards Organization (NISO) JATS Standing Committee (with participation from members of the Standards Tag Suite (STS) and Book Interchange Tag Suite (BITS) committees and some other invited experts) was formed, in 2021, with the goal of recommending changes to JATS to enable it to usefully encode multilingual articles. The subcommittee has recommended a set of changes that introduce new structures that can be available to JATS users who need them while minimizing the burden JATS users who rarely deal with multilingual content. Most of these changes are backward compatible with earlier versions of JATS. These changes are currently a work in progress and may become available in a future version of JATS. This paper presents a proposal for improving JATS to better support tagging multilingual articles with the hope of garnering feedback and suggestions from the JATS community.